2014
DOI: 10.1080/0020739x.2014.914253
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical speech and practical action: a case study of the challenges of including mathematics in a school technology project

Abstract: This paper presents a case study of how a teacher and nine-year-old students deal with mathematics in a practical technology project. By analysing videotaped dialogues between teacher and a pair of students working on constructing a house model, we identify challenges of meaningful inclusion of mathematics in the project. The dialogues are analysed in terms of an analytical framework where four categories of interaction patterns are combined with two main paradigms of mathematics teaching: the exercise paradig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Differences in ability, motivation, and background knowledge make it difficult to develop students’ knowledge without excluding considerable parts of the class. It is observed that when a teacher engages in a dialogic exchange of views with specific students, other students often stop paying attention (Bungum, Manshadi, & Lysne, ; Sedova et al., ). Hence, the characteristic of dialogic teaching being reciprocal as described by Alexander () may clash with the criterion of being collective .…”
Section: Dialogues For Learningmentioning
confidence: 99%
“…Differences in ability, motivation, and background knowledge make it difficult to develop students’ knowledge without excluding considerable parts of the class. It is observed that when a teacher engages in a dialogic exchange of views with specific students, other students often stop paying attention (Bungum, Manshadi, & Lysne, ; Sedova et al., ). Hence, the characteristic of dialogic teaching being reciprocal as described by Alexander () may clash with the criterion of being collective .…”
Section: Dialogues For Learningmentioning
confidence: 99%